2021
DOI: 10.1177/13548565211003878
|View full text |Cite
|
Sign up to set email alerts
|

Moonwalking together: Tracing Redditors’ digital memory work on Michael Jackson

Abstract: This article investigates the memory work concerning Michael Jackson on Reddit. By means of their posts, comments, and replies, people contributing to this site – Redditors – enter into a process we call mnemonic stabilization. This is a collaborative process in which networked individuals share their memories about, in this case, Michael Jackson. We argue that this process resembles Jackson’s dance technique called moonwalking: Redditors seem to go back in time, but they continually alter how Jackson is remem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Even though he turned into a man with feminine look, Michael Jackson is still praised by the people because of his songs and choreography. Jackson was able to demonstrate high skills in singing and dancing [36]. Dreaming of following Jackson"s success career in singing and danacing, many artists are trying to build their careers and fame by imitating Michael Jackson"s choreography [37].…”
Section: Discussionmentioning
confidence: 99%
“…Even though he turned into a man with feminine look, Michael Jackson is still praised by the people because of his songs and choreography. Jackson was able to demonstrate high skills in singing and dancing [36]. Dreaming of following Jackson"s success career in singing and danacing, many artists are trying to build their careers and fame by imitating Michael Jackson"s choreography [37].…”
Section: Discussionmentioning
confidence: 99%
“…As becomes apparent here, the socio-technical infrastructures of social networks are profoundly implicated in digital memory work. Calling attention to this as 'work', as we have done in this section (following Smit, 2020), highlights the continually emergent nature of digital memory, not only for individuals or groups, but also in relation to technologies and objects (Esteve Del Valle and Smit, 2021). Prey and Smit observe this adroitly when they recognise that although Facebook is a platform through which 'we compose ourselves', it is, at the same time 'composing us', in large part through its 'proprietary algorithms' (2018: 218).…”
Section: Social Media Memory 'Work'mentioning
confidence: 98%
“…In the case of Deep Nostalgia especially, the frenetic social media sharing which occurred around its launch demonstrated that shift extraordinarily well, with what might have started as ‘intimate’ remembering (Hjorth and Hinton 2019: 172) transferring quite comprehensively – and in the case of DeepStory also quite audibly – into the public domain. This is significant because it requires that memories and remembering are shaped to fit the socio-technical parameters of social platforms (Esteve del Valle and Smit 2021), and it demonstrates how – through what might be termed ‘posthumous performances’ – the dead continue to be made productive, ‘generat[ing] capital’ for these companies ‘in collaboration with the living’ (Stanyek and Piekut 2010: 14).…”
Section: Myheritage Generative Ai and Ethical Considerationsmentioning
confidence: 99%
“…Our analysis in this article draws on studies of digital memory which emphasise the manifold ways mediated memories now have a generative function in our everyday lives; 'creating and re-creating a sense of past, present, and future of ourselves in relation to others ' (van Dijck 2007: 21). 1 Mediated memories, according to Worcman and Garde-Hansen (2016) 'stretch' the very idea of the past, such that it becomes 'continually emergent', not least within the socio-technical parameters of platforms (Esteve Del Valle andSmit 2021: 1816). Of particular relevance for this discussion are works studying interconnections between algorithms, automation and memory (Kidd and Nieto McAvoy 2023;Cheney-Lippold 2017;Lambert et al 2018;Sisto 2020Sisto , 2021 as well asgiven encouragements to share synthetic media creations via social mediaon the impacts of memory metricization or quantification within those contexts (Jacobsen and Beer 2021a).…”
Section: Introductionmentioning
confidence: 99%